PENINGKATAN HASIL PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIVE TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) - aprizan -; Mulza Rois; Futri Nurjanah (Jurnal Tunas Pendidikan, 2019)
Social Sciences (IPS) are very important subjects taught in elementary schools, to prepare and foster students to become good citizens. The background problem in this study is the low learning outcomes of social studies. This study aims to describe the improvement of the process and results of social studies learning by using the STAD Cooperative learning model in class V SDN No. 109 / II Mangosteen Bathin III District. This research is a Classroom Action Research (CAR) with four stages of activities namely planning, action, observance and reflection. The results of the data analysis can be concluded that the application of the STAD Cooperative learning model can improve the learning process and the results of social studies in class V A SDN 109 / II Manggis Bathin III subdistrict Bungo Regency